Economic Empowerment Of Communities Around Islamic Boarding School - Ahmad Munib Syafa’at, Sebastiana Viphindrartin, Mohammad Saleh, Rafael Purtomo Somaji (International Journal of Advanced Science and Technology, 2020)
Economic empowerment is very important in efforts to reduce poverty. The existence of the Darussalam Islamic Boarding School Blokagung Banyuwangi East Java Indonesia, which has been established since 1951, currently has 6823 santri based on education units from all across the archipelago and neighbouring countries. The existence of Darussalam Islamic Boarding School becomes fresh air for the community around the Islamic Boarding School. The purpose of this study is to analyze statistically descriptive about the economic potential of the community around the Islamic Boarding School to determine the extent of community economic empowerment around the Islamic Boarding School Darussalam, Banyuwangi, East Java, Indonesia. The data used are primary and secondary data with the number of research respondents taken by simple random sampling of 108 people. The results showed that economic empowerment around the economy around the Islamic Boarding School had contributed to the income of the community wherein 3 hours of economic transactions every morning at 04.30-07.30 WIB which was carried out in the Darussalam traditional market, Blokagung Hamlet, Karangdoro Village, Tegalsari District, Banyuwangi Regency, East Java, Indonesia financial circulation circulating in the market around Rp. 22,825,000. The economic empowerment of the community must continue to be strengthened to improve welfare both economically and socially in the communities around the Islamic Boarding School.